Analyzing student learning style profiles for differentiated learning in merdeka curriculum in elementary schools - Susanti, Atika; Darmansyah, Ady; Naqsyahbandi, Fajar; Muktadir, Abdul (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Students have unique learning styles. Understanding students' learning style profiles enables teachers to design differentiated learning with more effective teaching strategies that cater to individual needs, enhancing comprehension and retention of material. The aim of this research is to determine the Student Learning Style Profiles for Differentiated Learning in the Merdeka Curriculum in Elementary Schools. This is motivated by the distinct differences among students influenced by environmental factors and brain dominance, shaping learning styles towards visual, auditory, or kinesthetic preferences. This qualitative descriptive research employed a case study approach, involving all second-grade students (Class IIB) of elementary school 44 Bengkulu city in the academic year 2023/2024, totaling 24 students. Data collection methods included observation, interviews, and questionnaires. The research findings reveal diverse learning styles among second-grade students, with 31% being visual learners, 32% auditory, and 37% kinesthetic. These differences pose a challenge for teachers to implement differentiated teaching strategies. The goal of differentiated learning is to facilitate meeting the diverse learning needs of students. This study anticipates that students' learning styles in elementary school 44 Bengkulu city may differ in auditory and kinesthetic aspects, and understanding these learning styles can assist teachers in adapting their teaching approaches to meet students' needs and potentials.